1968
DOI: 10.1063/1.1691853
|View full text |Cite
|
Sign up to set email alerts
|

Jets and Wakes in Tailored Pressure Gradient

Abstract: Similarity solutions of the boundary-layer equations representing the flow of jets in an external stream and tailored pressure gradients were obtained. These solutions apply to jets in coflowing and counterflowing streams. A number of analytical solutions not previously published were obtained. Of particular interest are the solutions for small-increment jets which imply that a Gaussian velocity profile exists far downstream from the origin of the jet, even in arbitrary pressure gradient. The solutions were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is possible to define a normalized spreading parameter for the wake as S w = (U E /U o )dy h /dx, where U E is the outer stream velocity and U o is the velocity deficit at the centerline of the wake [53,54]. The simulation parameters for plane far wake simulations are specified in the paper by Zhou et al [54] as Re = 2800 and U i = 6.7 m/s.…”
Section: Plane Far Wake Resultsmentioning
confidence: 99%
“…It is possible to define a normalized spreading parameter for the wake as S w = (U E /U o )dy h /dx, where U E is the outer stream velocity and U o is the velocity deficit at the centerline of the wake [53,54]. The simulation parameters for plane far wake simulations are specified in the paper by Zhou et al [54] as Re = 2800 and U i = 6.7 m/s.…”
Section: Plane Far Wake Resultsmentioning
confidence: 99%
“…Measurements by these authors 22 indicated that in zero pressure gradient turbulent boundary layers, plane jets, wakes and mixing layers an eddy Reynolds number could be formed considering the turbulent fluid only, and that this Reynolds number was a constant for these flows. Briefly, hot wire measurements of the turbulent shear stress give T, while the actual shear stress in the turbulent fluid only is given approximately by i t = i/y where y is the intermittency distribution measured at the same streamwise station.…”
Section: Outer Regionmentioning
confidence: 97%